Hobbes and the tragedy of democracy - Holman, Christopher (2020)
This article reconsiders Thomas Hobbes's critique of the democratic sovereign form from the standpoint of what it identifies as the latter's most important ontological conditions: the lack of a transcendent source of fundamental law, and a natural human equality that renders all individuals competent to participate in legislative modes. For Hobbes these two conditions combine to render democracy a tragic regime. Democracy is tragic to the extent that it must be a regime of self-limitation, there existing no ethical standard external to society that may intervene so as to guide our political self-activity, and yet the structure of deliberation in democratic assemblies tends to render such self-limitation impossible. Hence what Hobbes sees as the inherent tendency of democratic activity to descend into excess and madness. This risk is an intrinsic potentiality embedded within democracy's very conditions, a fact covered up by much post-Hobbesian liberal democratic theory that attempts to normatively ground the democratic form in various universal principles of natural law or right.